SPAMMING DALAM PERSPEKTIF HUKUM PIDANA - Brahma Astagiri (Universitas Airlangga, 2010)
Sending e-mail is legal but sending unsolicited e-mail to many e-mail addresses (spamming) is illegal. There are some damages and displeasures affected to internet users caused by spam. Every e-mail every user has the right to use an e-mail as a communication media. It means that they have to use their right proportionally to avoid harassing other users. Activities of using an e-mail are always limited by obligation to respect other people’s rights. Considering this reason, some laws need to be effected to regulate spamming.